Genre analysis of research article introductions from the Malaysian journal of 'The English Teacher' and the international 'ELT Journal' / Raja Shahrul Bariah Raja Baniamin - Raja Baniamin, Raja Shahrul Bariah (2007)
Genre-based studies of academic texts have mainly focused on research articles written by native English writers. The objectives of this study are to examine the rhetorical structure of Malaysian research article introductions and to investigate the ways in which the rhetorical structure of Malaysian research article introductions may differ from the internationally published research article introductions. This study explores the relation of texts generic structure and the context. A corpora of 30 research articles were selected. For the purpose of conducting a comparative study, 15 introductions from locally published journal ‘The English Teacher’ and 15 from internationally published ‘ELT’ Journal' were taken. This study developed a framework for the generic structure analysis based on Swales CARS and OARO model. It was found that the international research articles complied with the CARS model whereas the Malaysian research article introductions adhered to the OARO model. It must be mentioned that two of the Malaysian introductions opaquely complied with the CARS model. This may be due to the exposure that the authors may have had in writing introductions the conventional way. Overall, the findings tend to confirm Swales’s claim that the research in the nonnative speakers’ world tend to be less antagonistic and thus geared more towards establishing readership rather than establishing the research. One prominent feature o f both ELT related introductions is that they are prone to discussing theories, personal experience and personal thoughts. As a result, new terms were proposed, CARDS - Create a Research Discussion Space and OARDO - Open a Research Discussion Option. The present study has significant implication for scholars’ writing o f RA introductions. Knowledge o f formal genre structure is useful particularly for scholars to achieve full control of their academic writing process. By comparing two different corpus, this study managed to sensitize scholars to the rhetorical structure of RA introductions in academic texts within the discipline of ELT.